The Anatomical Layering Assessment: The Construction of Beauty - de Sanctis Pecora C (Dove Medical Press, 2024)
Carla de Sanctis Pecora Dermatologie Private Practice, São Paulo, BrazilCorrespondence: Carla de Sanctis Pecora, Dermatologie Private Practice, Avenida Dr. Cardoso de Melo, 1308, conj 121, São Paulo, 04548-004, Brazil, Tel +5511 99621-9162, Email carla@dermatologie.com.brAbstract: Restructuring an aging face from bone structure to the surface of the skin can be metaphorically compared to building and renovating a house. While each anatomical layer of the face undergoes an aging process of its own, there is also an interdependency of superficial structures on deeper layers, so that a change in one layer may lead to changes to the adjacent layers. This interaction among the structures deep into the skin, along with the skin's ability to envelope them is what determine the aspect of the aging face. Thus, a careful assessment of all the layers is imperative and we describe herein a step-by-step facial layering assessment and facial restructuring approach from bone structure to the surface of the skin to implement a treatment plan able to deliver a harmonious rejuvenating outcome.Keywords: layers, assessment, anatomy, aging process, combined treatment